Effects of dimensions of basalt aggregates on concrete properties. Case of crushed stone and sand from the menchum river in North-West Cameroon - Casimir, Gouafo (European Journal of Applied Sciences, 2022)
This research work aims to compare the physical and mechanical properties of concretes, obtained from different dimensions of basalt aggregates. The results show that the concrete made from the 0/5 mm aggregate has the highest workability, followed by the 5/15 aggregate and the 5/25 aggregate. Also the concrete made from basalt gravel 5/25 mm; 5/15 mm and river gravel recorded mean compressive resistance of 31.4 Mpa, 28.35 Mpa and 26.35 Mpa respectively at 28 days and mean bending resistance of 3.35 Mpa, 2.78 Mpa and 2.49 Mpa respectively at 28 days. The strength of the concrete in compression and bending increases with the dimensions of the aggregates used. It was concluded the workability of fresh concrete decreased with increasing aggregate size, and the compressive and bending strength increased with increasing aggregate size with a water/cement ratio of 0.5. The compaction coefficient increases with grain size.